Coordinated frequency regulation for thermal power unit and battery energy storage using dynamic proportional control - Gangui Yan; Qianli Sha; Junhui Li; Zheng Fang; Shuaishuai Lv; Shuo Zhan; Lin Yue (International Journal of Electrical Power & Energy Systems)
This paper addresses the issues of significant frequency regulation losses, short lifespan and poor economic performance of battery energy storage system in the combined frequency regulation process with the thermal power unit by proposing a coordinated frequency regulation control strategy for the thermal power unit and battery energy storage system using data-driven and dynamic proportional control. First, the mechanism model and operational data are combined to design a data-driven automatic generation control frequency regulation characteristic model for the thermal power unit, and a coordinated frequency regulation system model for the thermal power unit and battery energy storage system is then constructed, tailored to the automatic generation control frequency regulation environment. Considering the state of charge of battery energy storage system, the dynamic proportional control strategy for the thermal power unit and battery energy storage system is designed. The frequency regulation loss cost of the thermal power unit is quantified, and an economic model for the thermal power unit and battery energy storage system is constructed. Hippopotamus optimization algorithm is applied to optimize the relevant parameters of the dynamic proportional control strategy, resulting in a control scheme that maximizes overall benefits. Finally, the effectiveness and superiority of the proposed strategy are validated using one month of actual operational data from a 330 MW unit in a power plant.